Precision medicine and parental experience: a longitudinal study of psychosocial responses to germline genomic results in pediatric oncology - Meaghann S. Weaver; Jessica S. Flynn; Jiaming Li; Gabrielle M. Armstrong; Lynn W. Harrison; Belinda N. Mandrell; Zachary T. Wooten; Liza-Marie Johnson; Kim E. Nichols; Katianne M. Howard Sharp (Frontiers in Medicine, 2026)
Introduction Precision medicine has become central to pediatric oncology, with germline genomic sequencing commonly integrated into routine care. Families must interpret complex genomic findings during emotionally vulnerable periods, generating mixed reactions ranging from clarity and relief to anxiety and uncertainty. Palliative care clinicians, genetic counselors, psychologists, social workers, and oncology providers may each contribute to supporting families as they interpret and integrate these findings over the course of a child’s cancer care and beyond. Little is known about the trajectory of parental emotional and cognitive responses after receiving germline sequencing results, limiting clinicians’ ability to anticipate support needs across the cancer care continuum. This study quantitatively examines parental emotional and cognitive responses across time following disclosure of germline sequencing results in a pediatric oncology setting. Methods Parents ( n = 218) self-reported sequencing-related distress, positive feelings, intrusive thoughts, certainty, and self-efficacy using validated measures at two longitudinal follow-up points after disclosure of their child’s germline test results. Outcomes were compared across germline test result types (pathogenic/likely pathogenic [P/LP], n = 31 [14%]; variants of uncertain significance [VUS], n = 86 [39%]; and negative, n = 101[46%]). Results Parents of children receiving P/LP or P/LP+VUS results reported significantly higher distress yet greater positive feelings than parents receiving negative results. Notably, certainty and self-efficacy increased from Timepoint 1 (median 254 days following return of results) to Timepoint 2 (median 537 days). Intrusive thoughts did not significantly differ by genetic result type or change over time; however, the factors contributing to intrusive thoughts could not be determined from the current study. Discussion These findings provide insight into how families adapt to germline genomic information following a pediatric cancer diagnosis. As precision medicine becomes increasingly embedded in pediatric oncology, structured follow-up and communication that address families’ evolving informational and psychosocial needs are essential to ensure care that is scientifically precise, emotionally attuned, and centered on the family experience.